The usage of morbid themes and imageries in contemporary art: a case study of “12: a group exhibition in anticipation of the 2012 apocalypse” - Syed, Kanwal; Abdullah, Sarena (MCSER Publishing, Rome-Italy, 2013)
Death and mortality have not only become a major trend in various forms of visual communication during contemporary times but almost an obsession. These themes of hopelessness, violent imagery and mortality of life have also been a prominent element of contemporary art scene since the arrival of critical post modernism in the 1980’s but it was not until the arrival of the 21st century that these themes took a strong hold. There are many factors that contributed to the contemporaneity’s fixation with morbidity and mortality. The absence of religious narratives in the modern society left a void in the lives of many creating a sense of despair. The failure of ideologies like socialism and communism which are replaced by consumer capitalism as an undesirable but only viable path ended the idealistic aspirations of turning the world into a better place collectively for all mankind. But the biggest blow on contemporary art came with the horrific incident of September 11 suicide attacks upon the soil of the United States. In the atmosphere of a world obsessed with the transience of life nothing could be more welcome than the Mayan myth, the end of the world on the eve of 21/12/12. In anticipation of the world coming to an end, an exhibition was arranged by 12 local artists from Penang, Malaysia. Using the exhibition as a case study this article examines the obsession of contemporary art with the mortality and transience of life and floats an apprehensive thought, is the sense of hopelessness and apocalypse on individual or collective level the only message contemporary artists have or is it just a commercial hype, in sync with the same capitalist consumer society it criticizes? Selling what sells nothing more nothing less?